TINJAUAN PERENCANAAN PERKERASAN LENTUR JALAN SIMPANG PASAR PARIAMAN SAMPAI DENGAN SIMPANG KELING KOTA PARIAMAN - Mhd Rijal Qadafi; Helga Yermadona; Ana Susanti Yusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The road is a very important factor for the community in carrying out their daily activities. Therefore, roads are very important and useful for the community, so the government is currently intensively building roads for the province of West Sumatra. starting from local roads, collector roads, arterial roads, which are being planned by regional heads or the government to fulfill economic activities and improve the quality of the economy in Indonesia. On the existing roads, there are still many holes in the road and the collapsed shoulder of the road and therefore the regional head is planning to open a new road between Pasar Pariaman Intersection to Keling Intersection, 931 meters long STA and 7.2 to 7 wide, 5 meters which will be planned for the life of the road for the next 20 years, and a solution is obtained that will facilitate and improve all transportation in the area. Calculating the thickness of the pavement at the Pariaman Intersection to the Kampung Keling Intersection with a length of 931 meters using the Component Analysis method and AASTHO 1993. And from the two methods which have a design life of 20 years, it can be obtained that the thickness of the layer calculated meets the requirements of the plan, namely D1 (Laston) = 7.5 cm D2 = 20 cm and D3 = 28 cm, while for the 1993 AASTHO method the calculated layer thickness is D1 = 12 cm D2 = 14 cm and D3 = 36 cm.Keywords: Thickness of road pavement, AASTHO 1993, Component Analysis